Endotracheal intubation using the C-MAC(® )video laryngoscope or the Macintosh laryngoscope: A prospective, comparative study in the ICU - Noppens, Ruediger R (BioMed Central, 2012)
INTRODUCTION: Endotracheal intubation in the ICU is a challenging procedure and is frequently associated with life-threatening complications. The aim of this study was to investigate the effect of the C-MAC(® )video laryngoscope on laryngeal view and intubation success compared with direct laryngoscopy. METHODS: In a single-center, prospective, comparative before-after study in an anesthetist-lead surgical ICU of a tertiary university hospital, predictors of potentially difficult tracheal intubation, number of intubation attempts, success rate and glottic view were evaluated during a 2-year study period (first year, Macintosh laryngoscopy (ML); second year, C-MAC(®)). RESULTS: A total of 274 critically ill patients requiring endotracheal intubation were included; 113 intubations using ML and 117 intubations using the C-MAC(® )were assessed. In patients with at least one predictor for difficult intubation, the C-MAC(® )resulted in more successful intubations on first attempt compared with ML (34/43, 79% vs. 21/38, 55%; P = 0.03). The visualization of the glottis with ML using Cormack and Lehane (C&L) grading was more frequently rated as difficult (20%, C&L grade 3 and 4) compared with the C-MAC(® )(7%, C&L grade 3 and 4) (P < 0.0001). CONCLUSION: Use of the C-MAC(® )video laryngoscope improved laryngeal imaging and improved the intubating success rate on the first attempt in patients with predictors for difficult intubation in the ICU setting. Video laryngoscopy seems to be a useful tool in the ICU where potentially difficult endotracheal intubations regularly occur.